Magical Imaginations - Guenther, Genevieve (University of Toronto Press, 2011)
In the English Renaissance, poetry was imagined to inspire moral behaviour in its readers, but the efficacy of poetry was also linked to 'conjuration,' the theologically dangerous practice of invoking spirits with words. Magical Imaginations explores how major writers of the period – including Spenser, Marlowe, and Shakespeare – negotiated this troubling link between poetry and magic in their attempts to transform readers and audiences with the power of art. Through analyses of texts ranging from sermons and theological treatises to medical tracts and legal documents, Genevieve Guenther sheds new light on magic as a cultural practice in early modern England. She demonstrates that magic was a highly pragmatic, even cynical endeavor infiltrating unexpected spheres – including Elizabethan taxation policy and Jacobean political philosophy. With this new understanding of early modern magic, and a fresh context for compelling readings of classic literary works, Magical Imaginations reveals the central importance of magic to English literary history.
10.3138/9781442693951